2011
DOI: 10.1142/s1793042111004113
|View full text |Cite
|
Sign up to set email alerts
|

NONSOLVABLE POLYNOMIALS WITH FIELD DISCRIMINANT 5A

Abstract: Abstract. We present the first explicitly known polynomials in Z[x] with nonsolvable Galois group and field discriminant of the form ±p A for p ≤ 7 a prime. Our main polynomial has degree 25, Galois group of the form P SL 2 (5) 5 .10, and field discriminant 5 69 . A closely related polynomial has degree 120, Galois group of the form SL 2 (5) 5 .20, and field discriminant 5 311 . We completely describe 5-adic behavior, finding in particular that the root discriminant of both splitting fields is 125 · 5 −1/12500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Further applications of the explicit study of Belyȋ maps have been found in inverse Galois theory, specifically the regular realization of Galois groups over small number fields: see the tomes of Matzat [120], Malle-Matzat [107], and Jensen-Ledet-Yui [80]. Upon specialization, one obtains Galois number fields with small ramification set: Roberts [131,132,133], Malle-Roberts [112], and Jones-Roberts [86] have used the specialization of three-point covers to exhibit number fields with small ramification set or root discriminant. The covering curves obtained are often interesting in their own right, spurring further investigation in the study of low genus curves (e.g., the decomposition of their Jacobian [127]).…”
Section: Background and Applicationsmentioning
confidence: 99%
“…Further applications of the explicit study of Belyȋ maps have been found in inverse Galois theory, specifically the regular realization of Galois groups over small number fields: see the tomes of Matzat [120], Malle-Matzat [107], and Jensen-Ledet-Yui [80]. Upon specialization, one obtains Galois number fields with small ramification set: Roberts [131,132,133], Malle-Roberts [112], and Jones-Roberts [86] have used the specialization of three-point covers to exhibit number fields with small ramification set or root discriminant. The covering curves obtained are often interesting in their own right, spurring further investigation in the study of low genus curves (e.g., the decomposition of their Jacobian [127]).…”
Section: Background and Applicationsmentioning
confidence: 99%
“…and minimal conductor N. Then N = p 5 p 7 , where p 5 = ((−2b 3 − 12b 2 + 31b + 25)/7) is the unique prime above 5 and p 7 = ((−2b 4 − 9b 3 + 8b 2 + 53b + 6)/7) is one of the five primes above 7. Roberts [50] showed that the mod 5 Galois representation…”
Section: Examplesmentioning
confidence: 99%
“…The elliptic curve E found by Roberts [50] was obtained from our computations of Hilbert modular forms at level p 5 over F . The space S 2 (p 5 ) new has 2 Hecke constituents of dimension 10 and 20, respectively.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation